Роль прототипу у Figma під час розробки дизайн макету - Князєва, А. О. (ХНУРЕ, 2025)
This work explores the significance of prototyping in Figma during the development of design mockups. It examines the key types of prototypes, including paper, low-fidelity, high-fidelity, and interactive, highlighting their ad vantages and limitations. Special emphasis is placed on Figma’s functionality as a powerful tool for creating, testing, and refining design mockups efficiently.
Keywords: Figma; дизайн макету